Violence and Latin‐American preadolescents: A study of social brain function and cortisol levels. Issue 5 (20th February 2019) - Buchweitz, Augusto; de Azeredo, Lucas Araújo; Sanvicente-Vieira, Breno; Metsavaht Cará, Valentina; Bianchini Esper, Nathália; Soder, Ricardo Bernardi; da Costa, Jaderson Costa; Portuguez, Mirna Wetters; Franco, Alexandre Rosa; Grassi‐Oliveira, Rodrigo
Abstract: The present study investigated exposure to violence and its association with brain function and hair cortisol concentrations in Latin‐American preadolescents. Self‐reported victimization scores (JVQ‐R2), brain imaging (fMRI) indices for a social cognition task (the 'eyes test'), and hair cortisol concentrations were investigated, for the first time, in this population. The eyes test is based on two conditions: attributing mental state or sex to pictures of pairs of eyes (Baron‐Cohen, Wheelwright, Hill, Raste, & Plumb, 2001). The results showed an association among higher victimization scores and (a) less activation of posterior temporoparietal right‐hemisphere areas, in the mental state condition only (including right temporal sulcus and fusiform gyrus); (b) higher functional connectivity indices for the Amygdala and Right Fusiform Gyrus (RFFG) pair of brain regions, also in the mental state condition only; (c) higher hair cortisol concentrations. The results suggest more exposure to violence is associated with significant differences in brain function and connectivity. A putative mechanism of less activation in posterior right‐hemisphere regions and of synchronized Amygdala: RFFG time series was identified in the mental state condition only. The results also suggest measurable effects of exposure to violence in hair cortisol concentrations, which contribute to the reliability of self‐reported scores by young adolescents. The findings are discussed in light of the effects of exposure to violence on brain function and on social‐cognitive development in the adolescent brain. A video abstract of this article can be viewed athttps://www.youtube.com/watch?v=qHcXq7Y9PBk Abstract : Our study shows, for the first time, an association of exposure to violence in Latin‐American preadolescents with differences in the neural underpinnings of social cognition: More violence was associated with less brain activation in RFFG and RSTS and significantly correlated with connectivity measures for amygdala‐RFFG activation; more violence was also associated with higher hair cortisol levels.